PENGELOLAAN KERJASAMA SEKOLAH DENGAN DUNIA USAHA / DUNIA INDUSTRI (STUDI SITUS SMK NEGERI 2 KENDAL) - Yulianto Yalianto; Budi Sutrisno (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The purpose of the study was to describe ( 1 ) the empowerment potential of schoolsupport cooperation with Du / Di , ( 2 ) implementation of SMK Negeri 2 Kendalcooperation with Du / Di .This research is qualitative, withEthnographic researchdesign. The research was conducted at SMK Negeri 2 Kendal . Resource persons / Principalresearch informants , HumasbinWaka , Waka Curriculum / WakaSarpras / WMM , Kakom /WG Prakerin / BKK / UP / Head of section / teacher , student / alumni. Data collectiontechniques using in-depth interviews , observation and documentation . Analysis of the datausing a model of interactive analysis , data reduction , data model and conclusion /verification carried along with the data collection process through a cyclic process . Test thevalidity of the data using techniques degree of confidence ( Credibility ) .The results of this study are( 1 ). Empowerment potential of supporting cooperationwith schools Du / Di : a) HR teacher earning potential , on the up grade each year through onthe job training ( OJT ) to industry . b ) There are still people who do not understand theschool in the implementation of QMS ISO in school . c ) Some students lack the motivationto work . d ) Empowerment of alumni has not been well organized and e ) Empowerment ofpotential schools managed by Swot analysis , strategies and actions to support theempowerment of cooperation with Du / Di is done through the implementation of the workprogram of the school and the field of public relations programs . ( 2 ) Implementation ofSMK Negeri 2 Kendal cooperation with Du / Di : a) Implementation of cooperationembodied in the MoU , chosen Du / The quality meets industry standards nationally /internationally b ) Validation and synchronization curriculum along with Du / Di / stakeholdersevery year . c ) Periodically once a year to bring Du / Di / alumni of becoming ateacher . d ) Students carry prakerin in Du / Di for 4 months . Monitoring and evaluationconducted by the school counselor once a month .e ) Du / Di be the examiner / assessor in thevocational practice exams ( UPK ) is currently the national exam ( UN ) annually .f) Eachyear a minimum of 2 teachers in each - sent follow each competency skills on the job training(OJT) in the industry. g ) Production Unit of the school is still not optimal and h ) Schoolsfacilitate / bring together graduates / alumni of the user ( corporate headhunter ) through aspecial job fair ( BKK ) .